Kampanye Peningkatan Pengetahuan Mahasiswa Undip, Udinus, dan Unika terhadap Bus Wisata Kota Semarang sebagai Alternatif Stress Relief dalam Peran sebagai Creative/Copywriter, Finance Manager, Dan Video Editor - Thiara Virgietha Putri; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
Students are a group that is vulnerable to academic and social pressures, making recreationalactivities important as a form of stress relief. One of the recreational alternatives available inSemarang City is the Semarang City Tour Bus, which provides a free and educational city tourservice. However, preliminary research shows that the level of student awareness of this service isstill relatively low. Based on a survey of 115 students from Diponegoro University Pleburan, DianNuswantoro University, and Soegijapranata Catholic University, only around 20% of respondentswere aware of the existence of the Semarang City Tour Bus. Therefore, this field project aims toincrease students’ knowledge of the Semarang City Tour Bus as an alternative form of stress reliefthrough the implementation of an integrated communication campaign. The campaign was carriedout from December 2025 to March 2026 using communication strategies that combine cyber publicrelations, advertising, event and experiences, and collaboration with Key Opinion Leaders (KOL). Inthis field project, the author took roles as Creative/Copywriter, Finance Manager, and Video Editor,responsible for developing visual concepts, managing the campaign budget, and editing onboardinfotainment videos. The results show that the implemented communication strategies were able toincrease students’ knowledge and encourage their interest in utilizing the Semarang City Tour Bus asa recreational facility and an alternative means of stress relief.